The efficiency of radiation shielding made from materials with high atomic number and low mass density - Rudychev, V.G.; Azarenkov, M.O.; Girka, I.O.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2021)
The radiation shielding from γ-quanta of the existing transport containers (TC) for transportation of spent nuclear fuel (SNF) is made of steel or steel plus Pb 25…30 cm thick and weighting ⁓ 60…80 t. The application of materials with high atomic number, dispersed (solids grinded to a powdery state) to the densities in the range 4 < ρ < 8 g/cm³, is investigated. Simulations based on the Monte Carlo method show that at the densities of dispersed depleted U larger than 5 g/cm³ and shielding thicknesses of more than 30 cm, the absorption of γ-quanta of SNF is greater than that of the shielding made of steel of the same thickness. The application of such materials, while the weight characteristics of the shields are not exceeded, provides radiation shielding for SNF with the high burnup rate and the smaller cooling time or larger amount of the transported SNF. Радіаційний захист від гамма-квантів існуючих транспортних контейнерів (ТК) для перевезення відпрацьованого ядерного палива (ВЯП) виготовляється зі сталі або сталі і Pb товщиною 25…30 см і масою ⁓ 60…80 т. Досліджено застосування матеріалів з високим атомним номером, диспергованих (тверді частинки, подрібнені до порошкоподібного стану) до щільності в діапазоні 4 < ρ < 8 г/см³. Моделювання методом Монте-Карло показує, що при щільності диспергованого збідненого U більше, ніж 5 г/см³ і товщині захисту більше 30 см поглинання гамма-квантів ВЯП більше, ніж у захисту зі сталі такої ж товщини. Застосування таких матеріалів при неперевищенні вагових характеристик забезпечує радіаційний захист для ВЯП з високим ступенем вигоряння і меншим часом витримки або великою кількістю ВЯП, що транспортується. Радиационная защита от гамма-квантов существующих транспортных контейнеров (ТК) для перевозки отработавшего ядерного топлива (ОЯТ) изготавливается из стали или стали и Pb толщиной 25…30 см и массой ⁓ 60…80 т. Исследовано применение материалов с высоким атомным номером, диспергированных (твердые частицы, измельченные до порошкообразного состояния) до плотностей в диапазоне 4 < ρ < 8 г/см³. Моделирование методом Монте-Карло показывает, что при плотностях диспергированного обедненного U больше, чем 5 г/см³ и толщине защиты более 30 см поглощение гамма-квантов ОЯТ больше, чем у защиты из стали такой же толщины. Применение таких материалов при непревышении весовых характеристик обеспечивает радиационную защиту для ОЯТ с высокой степенью выгорания и меньшим временем выдержки или большим количеством транспортируемого ОЯТ.